Trauma of Literary History - Božić Blanuša, Zrinka (2009)
The discourse of literary historiography has been forced to transform during the past few decades. Disputing its representative claim, Foucault criticized the traditional model of historical change based on a continuous development. Other “ prophets of extremity” announced the end of narrative as well as of identity forms shaped through its restrictions. However, as if rejecting to confront the problem of the lost or absent totality, the comprehensive literary history continued to be sponsored, produced and published. On the other hand, the postmodern (encyclopedic) literary history may be taken as another, more reflective way of coming to terms with this traumatic experience. Instead of offering a monologist narrative synthesis of a given national literature, literary period or author, it becomes the site of a permanent dialogue. In order to explain this dialogic relationship between the history and the object of its inquiry, Dominick LaCapra implemented the psychoanalytic concept of transference. Thus he elucidated the implication of history in its object, especially its tendency to compulsively i.e. through identification repeat certain dimensions of its object. The purpose of this paper is to explore the delineated traumatic symptoms in the field of literary history as well as to question the possibilities of literary history to cope with this traumatic experience.
Projekt MZOS
ENG